Peran Kepuasan Kerja sebagai Mediasi antara Work Life Balance dan Burnout terhadap Kinerja Driver Generasi Z pada ShopeeFood di Kota Semarang - Natasya Cantika Sifaputri; Aris Puji Purwatiningsih; Masitha Fahmi Wardhani; Raden Ayu Aminah Rizkia Puspita Sari (Jurnal EMT KITA, 2026)
The gig economy phenomenon has increased work pressure among Generation Z ShopeeFood drivers, making work-life balance and burnout important factors affecting performance. This study aims to analyze the role of job satisfaction as a mediating variable in the relationship between work-life balance, burnout, and the performance of Generation Z ShopeeFood drivers in Semarang City. A quantitative approach was employed using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) method. Data were collected through a Likert-scale questionnaire from 137 respondents. The results indicate that work-life balance and burnout have a significant positive effect on both job satisfaction and performance. Job satisfaction also has a significant positive effect on performance and mediates the relationship between work-life balance, burnout, and performance. These findings suggest that the performance of Generation Z ShopeeFood drivers is influenced both directly by work-life balance and burnout and indirectly through job satisfaction. Therefore, maintaining work-life balance, managing work pressure, and improving job satisfaction are important factors in enhancing driver performance.